Dynamics of Water, Salt, and Nutrients Exchange at the Inlets of Three Coastal Lagoons - Maria Zoidou; Nikolaos Kokkos; Georgios Sylaios (Journal of Marine Science and Engineering, 2022)
The intertidal patterns at the inlet of three coastal lagoons (Agiasma, Porto Lagos, and Xirolimni) in Northern Greece were investigated by combining in situ samplings and computational efforts. These lagoons are Mediterranean, microtidal coastal systems, connected with the adjacent open sea (Thracian Sea) through their inlet canals and are highly affected by the lagoon–sea exchange processes. Limited freshwater enters their basins, mostly due to precipitation and agricultural drainage. An intense monitoring program of water flow and quality at the mouth of the three lagoons was carried out, aiming to quantify the transport mechanisms of water, salt, and nutrients across the inlet canal under different tidal/meteorological conditions. Ebb currents were recorded higher than flood currents, and the temporal variability of the longitudinal velocity was characterized by asymmetries. Residual currents were important to the water exchange, with the Eulerian water, salt, and nutrient fluxes being an order of magnitude larger than the Stokes drift. Eulerian transport and tidal pumping are considered as important mechanisms for salt and nutrients exchange through the inlets. The return flow factor varied from 1 to 17.5% of the water exiting the lagoons in ebb, while the residence time ranged from 0.7 days to 4.2 days.